ANALYSIS OF THE EFFECT OF SERVICE QUALITY, PRICE PERCEPTION, AND PROMOTION ON CONSUMER SATISFACTION - Ayu, Nirendra Dyah; Setianingsih, Wahyu Eko; Fatimah, Feti (Univesitas Muhammadiyah Tangerang, 2024)
In facing increasingly tight business competition, companies are required to continue to improve service quality, offer competitive prices, and carry out effective promotions to maintain customer satisfaction. This is very relevant in the tourism industry, especially in the vehicle rental service subsector, where service quality, price perception, and promotion play an important role in influencing customer satisfaction. This study aims to identify the effect of service quality, price perception, and promotion on customer satisfaction at BROW Tours and Travel Lumajang. This study uses a quantitative approach involving 85 participants. Data testing was carried out using multiple linear regression analysis and classical assumption tests. The results of the study indicate that service quality, price perception, and promotion have a positive and significant effect on customer satisfaction. Therefore, BROW Tours and Travel is expected to continue to improve service quality, adjust pricing strategies, and carry out more effective promotions to increase customer satisfaction.Keywords: Service Quality; Price Perception; Promotion; Satisfaction